Molecular orbital perspective for inner shell couplings: Level diagrams. (July 2015) - Verma, Punita; Safvan, C P; Jhingan, A; Nandi, T; Mandal, A
Synopsis: Level diagrams drawn for the Ag-Gd, Ho and Yb collision systems allow a qualitative explanation for the experimentally observed enhanced target and projectile cross sections. Super heavy quasimolecules formed during these slow, heavy-ion, heavy-atom collisions act as a beacon of light to investigate the couplings of the inner shells and the dependence of inner shell ionization on projectile charge state.